Lp Bounds for the Commutators of Oscillatory Singular Integrals with Rough Kernels - Yanping Chen; Kai Zhu (Abstract and Applied Analysis)
We establish the Lp boundedness for some commutators of oscillatory singular integrals with the kernel condition which was introduced by Grafakos and Stefanov. Our theorems contain various conditions on the phase function.